Tirzepatide: Dual GIP/GLP-1 Receptor Agonists, from Molecular to Clinical Practice for Treating Type-2 Diabetes and Obesity - Muhammad Aron Pase (PP PERKENI, 2024)
Tirzepatide is a promising drug with dual-acting glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) receptor activation that has revolutionized the treatment of type 2 diabetes mellitus (T2DM). In phase 3 clinical trials (SURPASS 1-5), tirzepatide has been shown to achieve better glycaemic control in terms of glycosylated hemoglobin reduction (HbA1c) and improved fasting, postprandial glucose levels and weight reduction as compared to placebo and active comparators. The SURPASS 4 clinical trial has shown positive cardiovascular outcomes in people with T2DM with elevated cardiovascular risk. Tirzepatide has acceptable side effects and is well tolerated, with a low risk of hypoglycaemia. Additionally, encouraging results from SURMOUNT trials and ongoing SURPASS-CVOT studies will shed more light on cardiovascular safety in the future. In this review, we have summarized the pharmacology, efficacy, safety, and clinical trials for potential impact for clinical treatment T2DM.